Therapeutic Opportunities of GPBAR1 in Cholestatic Diseases - Zhang, Fangling; Xiao, Xiaolin; Li, Yong; Wu, Hefei; Deng, Xinyu; Jiang, Yinxiao; Zhang, Wenwen; Wang, Jian; Ma, Xiao; Zhao, Yanling (Frontiers in Pharmacology, 2022)
GPBAR1, a transmembrane G protein-coupled receptor for bile acids, is widely expressed in multiple tissues in humans and rodents. In recent years, GPBAR1 has been thought to play an important role in bile homeostasis, metabolism and inflammation. This review specifically focuses on the function of GPBAR1 in cholestatic liver disease and summarizes the various pathways through which GPBAR1 acts in cholestatic models. GPBAR1 mainly regulates cholestasis in a holistic system of liver-gallbladder-gut formation. In the state of cholestasis, the activation of GPBAR1 could regulate liver inflammation, induce cholangiocyte regeneration to maintain the integrity of the biliary tree, control the hydrophobicity of the bile acid pool and promote the secretion of bile HCO3-. All these functions of GPBAR1 might be clear ways to protect against cholestatic diseases and liver injury. However, the characteristic of GPBAR1-mediated proliferation increases the risk of proliferation of cholangiocarcinoma in malignant transformed cholangiocytes. This dichotomous function of GPBAR1 limits its use in cholestasis. During disease treatment, simultaneous activation of GPBAR1 and FXR receptors often results in improved outcomes, and this strategy may become a crucial direction in the development of bile acid-activated receptors in the future.